Faktor Risiko yang Mempengaruhi Lama Penyembuhan Luka Perineum pada Ibu Post Partum - Anur Rohmin; Baity Octariani; Morlina Jania (Jurnal Kesehatan, 2017)
Perineal trauma is an injury that occurs in the perineum during delivery and it happened  70% among woman who labors vaginally. The perineal wound was healed when the wound is to be dry, no redness, no swelling, tissue fused and cured ≤7 days post-partum. The aim of this study to find out the influenced factors of the length perineal wound healing in post partum mothers. This study carried in 10th March until 11th July 2016. Methode: A  survey analytic design with cross sectional design was used in this study. The samples of this study were 128 post partum. others. Data were analyzed by univariate, bivariate using Chi-square and multiple logistic regression. The results of this study found that mothers who the length of perineum wound ≤ 7 days (62.5%) and >7 days (37.5%). Based on bivariate analysis there were a significant relationship between age, early mobilization, parity and kind of wound (p <0.05). Based on the multivariate analysis the most influencing factor was early mobilization (OR 7.613). The suggestion of this study is increasing the awareness of mother to do early mobilization.